A new species of Mimulus L. (Section Simiolus, Phrymaceae) from northeastern Michoacan, Mexico - Pérez-Calix, Emmanuel; Zamudio, Sergio (Instituto de Ecología, A.C., 2011)
Mimulus minimus is described and illustrated as a new species based on plants collected in the northeastern mountains of Michoacan state, Mexico. It grows in wet sites in the Pinus-Quercus-Cupressus forest. The new species is included in the section Simiolus Greene (subgenus Synplacus Grant). Its similarities and differences with morphologically more closely related species such as Mimulus calciphilus Gentry, M. depressus Phil., M. glabratus Kunth, M. minutiflorus Vickery, M. wiensii Vickery and M. yecorensis Vickeri and M. guttatus DC. are discussed.